REAKSI PASAR TERHADAP HARGA SAHAM SEBELUM DAN SETELAH PUBLIKASI LAPORAN KEUANGAN AUDITAN - Dewi, Tiara Kusuma; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2016)
The audit report is the depiction of the media to communicate to auditor and users of financial statement. The audit reports can reflect the condition of a company. The informations in the audit reports can be use as one analyzer for investor to take a decision to invest. Sampling use purposives samplings methods, the numbers of observation obtained 122 observation of the entire company list on the Indonesia Stock Exchanges. The data used in this research is secondarry data came  Yahoo Finance in 2013 and its audited financial statements through the website address www.idx.co.id.Penelitian analisaevent engineering study utilizes the result is there are differences in stock prices before and after the publication of financial statements audited the company that has an unqualified opinion, there are differences in stock prices before and after the publication of the audited financial statements on a company that has a qualified opinion, and there is a difference between a company's stock price has unqualified opinion and qualified opinion.
Keywords: unqualified audit report, a qualified audit report, stock prices and event study